Factors associated with receipt of second-line recurrent or metastatic cervical cancer treatment in the United States: A retrospective administrative claims analysis - Kalyani Sonawane; Tara Castellano; Christina Washington; Jie Ting; Andy Surinach; Carol Kirshner; Jagpreet Chhatwal; Turgay Ayer; Kathleen Moore (Elsevier, 2022)
Purpose: Contemporary, real-world data on eligible patients receiving treatment following progression on first-line (1L) recurrent or metastatic cervical cancer (r/mCC) therapy are needed to inform treatment algorithms and identify potential gaps in the r/mCC care continuum. Methods: This study estimated the prevalence and predictors of second-line (2L) r/mCC therapy among 1L-treated patients using the 2015-2020 IBM MarketScan® commercial claims database. Women ≥ 18 years diagnosed with cervical cancer and treated with first-line systemic therapies were identified and followed for 12 months from their 1L therapy end date. Women with claims for a new therapy after 60 days but no later than 365 days from the end of 1L treatment were identified as those who progressed and received 2L therapy for r/mCC. Descriptive statistics examined baseline cohort characteristics and multivariable logistic regression model examined the factors associated with receiving 2L treatment. Results: We identified 384 1L-treated patients with r/mCC with ≥ 12 months of follow-up post-1L treatment. During follow-up, over half (51.0 %) of the 1L-treated r/mCC patients received 2L treatment. Patients from the South and Midwest had a lower likelihood of receiving 2L treatment compared with those living in the Northeast (adjusted odds ratio [aOR] = 0.43; 0.23-0.84) and (aOR = 0.52; 0.28-0.95, respectively). Patients not treated with bevacizumab in 1L were also less likely to receive 2L therapy (aOR = 0.65; 0.43-0.99). Conclusion: Additional research and targeted outreach efforts are needed to understand geography-, population-, or practice-specific barriers impacting access to 2L therapy among patients with r/mCC.